Scapular morphometry- A study in West Bengal population with literature review - Ananya Biswas; Anwesa Pal; Hironmoy Roy; Indra Datta; Asis Kumar Ghoshal (Al Ameen Medical College, 2021)
Background: Scapula is a bone of interest for anatomists as it has a considerable evolutionary modification from quadruped to biped. It is the link bone between axial and appendicular skeleton of upper limb. Its different morphometric parameters were found to be associated with different diseases of the shoulder girdle. Till date no anthropometric data is available from the eastern India specifically from Bengalee population. Objective: Measurement of different morphometric parameters of dry human scapulae including its indices to elicit data from West Bengal. Methods: In the present study authors measured different parameters in 200 available dry human scapulae; preserved in Anatomy departments of different medical colleges of Kolkata over last one year. Measurement of length, breadth, infraspinous length, projection length and were taken by slide callipers, with calculation of scapular and infraspinous indices. Result: In the present study mean values of the parameters of scapula were: length 132.97±18.07mm, breadth 97.96±9.38mm, infra-spinous length 103.57±11.05mm, projection length 124.93±7.41mm, scapular index 75.56±17.67 and infra-spinous index 95.35±11.21. Conclusion: Measurement of different parameters of scapula and indices of scapula can be useful for surgical intervention, prosthetic invention, medico-legal aspect and in comparative study. In addition to the anthropometric data available for population from other zones of India, this study adds the data from Eastern India.